The impact of corporate governance quality on capital structure choices: does national governance quality matter? - Nguyen An; Tuan Nguyen; Phuong Hoang (Cogent Economics & Finance, 2022)
This research investigates the moderating effect of national governance quality on the corporate governance-capital structure decision relationship. Using an instrumental variable estimation technique to analyze a multinational dataset containing 23,142 firm-year observations of 3,270 firms in 59 economies from 2004 to 2014, we find evidence for the moderating role of national governance quality. Specifically, a well-functioning firm-level governance system tends to force managers to increase borrowing toward an optimal level for shareholders. The strength of the force, however, seems to decrease as national governance quality increases. Our findings suggest that a transparent and investor-friendly business environment created by the government may complement the firm-level corporate governance mechanism by reducing agency problems, thus reducing the need to use leverage as a tool to discipline managers. The results are robust to different proxies for national governance quality, corporate governance quality, and firm leverage.
Keywords: C23; G30; G32; G34; 330; capital structure; leverage; corporate governance quality; national governance quality; national institutions